Transmission dynamics of the monogenean Gyrodactylus salaris under seminatural conditions. Issue 6 (12th July 2014) - Hendrichsen, D K; Kristoffersen, R; Gjelland, K Ø; Knudsen, R; Kusterle, S; Rikardsen, A H; Henriksen, E H; Smalås, A; Olstad, K
Abstract Tracking individual variation in the dynamics of parasite infections in wild populations is often complicated by lack of knowledge of the epidemiological history of hosts. Whereas the dynamics and development of Gyrodactylus salaris Malmberg, 1957, on Atlantic salmon, Salmo salar L., are known from laboratory studies, knowledge about infection development on individual wild fishes is currently sparse. In this study, the dynamics of an infection of G. salaris on individually marked Atlantic salmon parr was followed in a section of a natural stream. During the 6‐week experiment, the prevalence increased from 3.3 to 60.0%, with an average increase in intensity of 4.1% day−1. Survival analyses showed an initially high probability (93.6%) of staying uninfected by G. salaris, decreasing significantly to 37% after 6 weeks. The results showed that even at subarctic water temperatures and with an initially low risk of infection, the parasite spread rapidly in the Atlantic salmon population, with the capacity to reach 100% prevalence within a short summer season. The study thus track individual infection trajectories of Atlantic salmon living under near‐natural conditions, providing an integration of key population parameters from controlled experiments with the dynamics of the epizootic observed in free‐living living populations.